Clinical effect of a mouthwash containing Anacardium occidentale Linn. on plaque and gingivitis control: A randomized controlled trial - Carlos Eduardo Bezerra Gomes; Dhiogo Gonçalves Cavalcante; José Eduardo Girão Filho; Flávio Nogueira da Costa; Sérgio Luís da Silva Pereira (Wolters Kluwer Medknow Publications, 2016)
Background: Plaque-associated gingivitis is a prevalent disease and research in its treatment using herbal agents must be encouraged to verify which would be a useful addition to the current range or chemotherapeutic treatment options. Aims: The aim of this study was to evaluate the clinical effect of a mouth rinse containing 10% Anacardium occidentale (AO) Linn., a typical plant commonly found in the Northeast Region of Brazil, on the reduction of plaque and gingivitis in comparison to a gold-standard chemotherapeutic agent. Materials and Methods: Thirty normosystemic adult volunteers of both genders, who had a minimum of twenty natural teeth, aging between 18 and 32 years, were enrolled in this crossover, controlled, examiner-blind clinical study. They were randomly allocated into three groups: 10% AO Linn. (n = 10); 0.12% chlorhexidine digluconate (CLX, n = 10); or placebo (PB, n = 10). All volunteers were instructed to brush their teeth with a fluoridated dentifrice two times a day (12/12 h) and to rinse for 1 min with one of the mouthwashes (AO, CLX, or PB) 30 min after tooth brushing for 1 month. Plaque index (PLI) and gingival bleeding index (BLI) were recorded on days 0 and 30. Nonparametric Kruskal-Wallis and Wilcoxon tests (α = 0.05) were performed to evaluate statistical differences among groups. Results: There was a significant reduction (P < 0.05) on plaque and gingivitis at day 30 just in CLX ([PLI = 0.47 ± 0.16; -30%]; [BLI = 0.15 ± 0.09; -55.8%]) and AO ([PLI = 0.49 ± 0.21; -31%]; [BLI = 0.13 ± 0.10; -56.6%]) groups, but no statistically significant difference was observed among them (P > 0.05). Conclusion: Mouthwash containing 10% AO was effective as an antiplaque and antigingivitis agent, in a similar manner that 0.12% CLX.